2006
DOI: 10.1038/nn1640
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive sharing of recycling synaptic vesicles between presynaptic boutons

Abstract: The synaptic vesicle cycle is vital for sustained neurotransmitter release. It has been assumed that functional synaptic vesicles are replenished autonomously at individual presynaptic terminals. Here we tested this assumption by using FM dyes in combination with fluorescence recovery after photobleaching and correlative light and electron microscopy in cultured rat hippocampal neurons. After photobleaching, synapses acquired recently recycled FM dye-labeled vesicles originating from nonphotobleached synapses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
255
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(282 citation statements)
references
References 41 publications
26
255
0
1
Order By: Relevance
“…Retrospective immunocytochemistry revealed that contribution of vesicles from previously active terminals to nascent synapses represents the major mode of inhibitory presynaptic development. Whether recycled vesicles contribute to new excitatory synapse formation has not been determined, although recent work has shown that recycling vesicles can be shared among multiple preexisting neighboring excitatory boutons (Darcy et al, 2006;Staras et al, 2010). Further quantitative assays to determine the precise contributions of different vesicle pools to nascent inhibitory and excitatory synapses may prove insightful.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective immunocytochemistry revealed that contribution of vesicles from previously active terminals to nascent synapses represents the major mode of inhibitory presynaptic development. Whether recycled vesicles contribute to new excitatory synapse formation has not been determined, although recent work has shown that recycling vesicles can be shared among multiple preexisting neighboring excitatory boutons (Darcy et al, 2006;Staras et al, 2010). Further quantitative assays to determine the precise contributions of different vesicle pools to nascent inhibitory and excitatory synapses may prove insightful.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widelyused methods exploits FM-dyes, fluorescent reporters that readily bind to lipid membrane and are taken up into recycling vesicles during endocytosis to provide a functional readout of vesicle turnover [21][22][23] . One dye variant, FM1-43FX, also efficiently drives the polymerization of diaminobenzidine (DAB) when photoactivated, leading to the formation of an osmiophilic precipitate [24][25][26][27][28][29][30][31] . In this way, functional vesicle pools that were previously labelled with FM-dye can be directly identified in electron micrographs.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%
“…In this way, functional vesicle pools that were previously labelled with FM-dye can be directly identified in electron micrographs. This approach has been used extensively and highly successfully in cultured neurons 7,10,24,28,30,[32][33][34] , a number of large, peripheral terminals [26][27][28][29]31,[35][36][37] , and large central release sites such as calyx of Held 25 revealing important information about organizational principles of vesicle pools. However, only recently 38 has this method been successfully applied to small central synapses in native brain tissue, where neurons are retained in relevant circuits with defined cytoarchitecture.…”
Section: Labelling and Visualizing Functional Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicle supply to release sites seems to be primarily governed by diffusion, a conclusion that we propose to extend to the case of SGs. Nevertheless, actin modulates the recovery from synaptic depression at the calyx of Held (Sakaba and Neher, 2003) and controls the exchange of synaptic vesicles between different boutons (Darcy et al, 2006). Actin, which is concentrated at the periphery of clusters, could thus participate in the retention of synaptic vesicles arriving from the axon or from the presynaptic membrane via the recycling pathway.…”
Section: Mobility Of Synaptic Vesicles and Role Of Myova In Neuronsmentioning
confidence: 99%